Evaluating the effectiveness of a community-based intervention in changing the knowledge, attitude, norms, and practices related to anemia among adolescents in the selected blocks of the Gorakhpur district, Uttar Pradesh (Journal of Food and Dietetics Research, 2025)
Introduction: Adolescent girls are one of the most vulnerable groups for anemia. The high prevalence of anemia among  adolescent girls is caused by various factors, including inadequate nutrition, gender disparities, poor sanitation and  hygiene, and deeply rooted cultural and social norms. Therefore, anemia prevention and timely management require a  broad, multi-dimensional approach that addresses these determinants.  Objectives: The present study was conducted to assess the effectiveness of community-based intervention in improving  knowledge, attitudes, practices, and norms among adolescent girls (15-19 years) in the selected blocks of the Gorakhpur  district, Uttar Pradesh. Methods: A cross-sectional quantitative study was conducted in two intervention blocks (Khajani & Pipraich) of the  Gorakhpur district. A baseline survey was followed by 5 months of intervention, after which an endline survey was  conducted among unmarried adolescent girls (15-19 years). The baseline and endline surveys were conducted with a  minimum of 400 adolescent girls. Moreover, the education intervention was conducted across 120-150 villages of the  intervention district. The data were analyzed and presented as mean, and standard deviation (interquartile range), and  frequencies (percentages) using STATA version 16.0. Results: The findings indicate a significant improvement in healthy eating intentions, perceived behavior control and  social norms related to nutrition and anemia prevention from baseline to endline (p
Keywords: Anemia; social norms; healthy eating; intentions